The Quality of Public Services at the Public Service Mall - Geri Rivaldi; Antik Bintari; Neneng Yani Yuningsih (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study aims to analyze the quality of public services provided by the Investment and One-Stop Integrated Services Office through the Public Service Mall in West Bandung Regency in 2024. The research employs a qualitative approach with a case study method, utilizing data collection techniques such as in-depth interviews, observation, and documentation. Data analysis is conducted based on the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that the establishment of the Public Service Mall has improved service accessibility and integration; however, several fundamental shortcomings remain. The tangibles dimension reveals limitations in physical facilities and digital systems; reliability highlights delays in permit processing; responsiveness shows an inadequate complaint-handling system; assurance reflects generally competent staff performance; and empathy suggests the need for a more personalized approach to the public. These findings confirm that the quality of public services has not fully met public expectations, particularly regarding speed, convenience, and complaint resolution. Therefore, a sustainable, data-driven, and community-oriented service improvement strategy is essential to build a more professional, efficient, and human-centered public service.